5 Years of Educational Buildings conformant with the Efficiency House Plus Standard. Insights from the Accompanying Research. - Erhorn-Kluttig, Heike; Preuss, Jessica; Erhorn, Hans (My University, 2021)
Educational buildings built based on the “Efficiency House Plus” building standard generate more energy, according to the annual energy balance, than they need for their operation. A total of seven pioneering educational buildings with an exemplary function have been supported and scientifically evaluated since 2015 in the context of the Efficiency House Plus research initiative of the Federal Ministry of the Interior, Building and Community (BMI) and the Federal Institute for Research on Building, Urban Affairs and Spatial Development (BBSR) with funds from the Future Building innovation programme. In the newly published brochure “5 Years of Educational Buildings conformant within the Efficiency House Plus Standard – Insights from the Accompanying Research” they will now be for the first time compactly presented. The focus of the publication is on funded educational buildings. For the BBSR special publication, the Fraunhofer Institute for Building Physics IBP has carried out an interim assessment of the ongoing model projects. The aim was to work out, interpret and convey the diversity, properties and characteristics of the educational buildings examined. Planning concepts, building simulations and initial results from the real operation of the completed buildings, which have to go through a 24-month monitoring process after their completion, form the starting point for the scientific cross-evaluation. The brochure addresses anyone interested in the Efficiency House Plus building standard and in innovative building concepts.
Keywords: Plusenergiehaus; Schulgebäude; Hochschulgebäude; Schulzentrum; Forschungsgebäude; Energieeffizientes Bauen; Energetische Sanierung; Modellvorhaben; Evaluation; Begleitforschung